ATOMS: ALMA Three-millimeter Observations of Massive Star-forming regions – V. Hierarchical fragmentation and gas dynamics in IRDC G034.43+00.24. Issue 4 (11th November 2021) - Liu, Hong-Li; Tej, Anandmayee; Liu, Tie; Issac, Namitha; Saha, Anindya; Goldsmith, Paul F; Wang, Jun-Zhi; Zhang, Qizhou; Qin, Sheng-Li; Wang, Ke; Li, Shanghuo; Soam, Archana; et al.
ABSTRACT: We present new 3-mm continuum and molecular lines observations from the ATOMS survey towards the massive protostellar clump, MM1, located in the filamentary infrared dark cloud (IRDC), G034.43+00.24 (G34). The lines observed are the tracers of either dense gas (e.g. HCO + /H 13 CO +   J = 1–0) or outflows (e.g. CS J = 2–1). The most complete picture to date of seven cores in MM1 is revealed by dust continuum emission. These cores are found to be gravitationally bound, with virial parameter, α vir < 2. At least four outflows are identified in MM1 with a total outflowing mass of ∼45 M⊙, and a total energy of 1 × 10 47  erg, typical of outflows from a B0-type star. Evidence of hierarchical fragmentation, where turbulence dominates over thermal pressure, is observed at both the cloud and the clump scales. This could be linked to the scale-dependent, dynamical mass inflow/accretion on clump and core scales. We therefore suggest that the G34 cloud could be undergoing a dynamical mass inflow/accretion process linked to the multiscale fragmentation, which leads to the sequential formation of fragments of the initial cloud, clumps, and ultimately dense cores, the sites of star formation.